VISUAL ARTS LESSONS AS A MEANS OF DEVELOPING STUDENTS’ CREATIVE AND PROFESSIONAL ACTIVITY - Eshmatov Samariddin Hamza oʻgʻli (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the pedagogical and psychological foundations for enhancing students’ creative and professional activity in visual arts lessons. It examines the use of interactive teaching methods, project-based learning, motivational strategies, and individualized approaches to foster students’ artistic skills and creative thinking. The article also provides recommendations for creating a supportive and stimulating learning environment to maximize students’ professional-creative development.